Comparative study of scaling parameters and research output of selected highly- and moderately-cited individual authors - Sangwal, Keshra (Journal of Computer Sciences Institute, 2022)
The real data of cumulative citations ln of selected nth paper of individual N papers published by some highly- and moderately-cited individual authors are analyzed to compare Hirsch and Hirsch-type indices h, h1, hf and hm, and citation radii R and Rf from consideration of: (1) the number An of coauthors of the paper, (2) the normalization of citations ln and cumulative fraction lnf of citation of the nth paper by mean and median citations of the citations ln of all Nc cited papers, and (3) the determination of effective rank neff of the lnf citations. Analysis of the ln(n), lnf(n) and lnf(neff) data was also carried out by using a Langmuir-type function l = l0[1-aKn/(1+Kn)], where l denotes the citations ln and lnf of all cited Nc papers arranged in the decreasing order, a is an effectiveness parameter, K is the so-called Langmuir constant, n denotes the rank n or neff of citations and l0 is the value of l when n or neff approaches zero. For a comparison of the publication output of different authors it was found that the hm index is more consistent than other indices, and it can be normalized to account for the publication career of different authors. However, Langmuir-type function is not adequate for comparison of the publication output of different authors because it describes the rank-order distribution patterns satisfactorily in terms of two parameters. To compare the publication output of different authors independent of their career length t, it is suggested to use scaling parameters h/t, hf/t and hm/t.